The Role Of The Community In Enforcement Of Environmental Law - Kunarto; Mahmuda Pancawisma Febriharini; Mohammad Solekhan (International Journal of Educational Research & Social Sciences, 2022)
The community has an important role in enforcing environmental law; therefore, the community needs to be invited to continue to monitor and report various forms of violations of the environment and existing natural resources. The community has rights and obligations in the enforcement and management of the domain. This is because a party is affected in the development process, which often involves environmental sustainability. Related to this, problems arise, what is the role of the community in enforcing environmental law, as well as the obstacles faced in enforcing environmental law. It is necessary to have consistency from various parties related to environmental law enforcement, starting from laws and regulations, implementing officials, and community participation to answer these problems. The normative juridical research approach, descriptive-analytical research specifications, data collection through secondary data in the form of library research and documentation studies, and qualitative analysis methods. One of the emphases made by the community in enforcing environmental law is through environmental organizations, namely through lawsuits in court and with the right to sue, that in the context of implementing ecological management responsibilities by the pattern of partnerships, environmental organizations, the filing of the lawsuit is in the interest of function and preservation. Environment. It should be realized that enforcing the environmental law is not easy, so there are often obstacles, for example, rules that have not been maximally implemented, law enforcement officers who have not been able to have good insight and understanding to solve environmental problems, as well as from public awareness that is still lacking to care about the environment itself and is indifferent, when violations occur.